Analisis ‘Urf terhadap Tradisi Timang Pengantin di Kecamatan Rubaru Kabupaten Sumenep - Ummi Kulsum (Tafhim Al-'Ilmi, 2023)
This paper to describe the Timang Pengantin is one of the traditions that is currently in the spotlight and is phenomenal among Madurese soceety, especally in Rubaru Sumenep. This tradition is full of the philosophy of life of the local counity and s local wisdom. The aim of ths tradition is to strengthen ties of friendship, get to know each other and understand each other between the two extended families, so that togetherness is created between them. This reseasrch used a qualitative research methodology. Ths research was conducted by directly observing the research object where the researcher went directly to a predetermained research location. Then it is carried out in a planned systematic manner, directed at goal by observing, and covering this phenomenon. While ‘urf analysis of the pengantin tradition yield three classifications, namely as follows first, the tradition of the timang pengantin in Rubaru Sumenep  is famal a tradition in the from of an act, which is generally believed to be carried out by the people of Rubaru Sumenep. Second, the tradition of the timang pengantin in cluded in the khos, specifically the timang pengantin is only carried out by Madura community, especially Rubaru Sumenep and the three, timang of the timang pengantin are included in the fasid if ang saweran s consdered a debt, if it is not intended as ashodaqah then it can be classified of shohih. Keyword: ‘Urf, Tradition, Timang Pengantin.